2020
DOI: 10.1021/acs.orglett.0c00679
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Borylation of Aryl Ethers via Cleavage of C–O Bonds

Abstract: Herein, we report the iron-catalyzed borylation of aryl ethers and aryl amines via cleavage of C−O and C−N bonds. This protocol does not require the use of Grignard reagents and displays a broad substrate scope, which allows the late-stage borylation. It also provides facile access to multisubstituted arenes through C−H functionalization using 2-pyridyloxy as the directing group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Moreover, the mixture of this reaction was monitored by 11 B NMR, and a suspected iron-boron complex 94 was observed ( 11 B NMR, δ = 22; for details, see Supporting Information). On the basis of these preliminary results and our previous studies, 58,59 a mechanism was proposed in Scheme 4. An iron alkoxide ate complex I was obtained through the reaction of t-BuOLi with FeI 2 .…”
Section: Fesupporting
confidence: 51%
See 2 more Smart Citations
“…Moreover, the mixture of this reaction was monitored by 11 B NMR, and a suspected iron-boron complex 94 was observed ( 11 B NMR, δ = 22; for details, see Supporting Information). On the basis of these preliminary results and our previous studies, 58,59 a mechanism was proposed in Scheme 4. An iron alkoxide ate complex I was obtained through the reaction of t-BuOLi with FeI 2 .…”
Section: Fesupporting
confidence: 51%
“…In our previous work, 58,59 we found that the iron-boronate complex with high reduction potential could promote the borylation of unactivated Csp 2 -O bonds. Inspired by this finding, we envisioned that the iron-boron ate complex might also induce the C-Cl bond cleavage, and this catalytic system could avoid the use of organometallic reagents to produce the low-valent iron species.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, the Feng group reported an iron-catalyzed borylation via activation of CÀ N and CÀ O bonds (Scheme 15). [55] Scheme 12. Fe/Cu co-catalyzed borylation of aryl bromides.…”
Section: Iron-catalyzed Csp 2 à B Bond Formationmentioning
confidence: 99%
“…Recently, the Feng group reported an iron‐catalyzed borylation via activation of C−N and C−O bonds (Scheme ) . The inert C−N bond could occur the borylation reaction via iron catalysis, but this transformation proceeded with low efficiency, and only 21% yield of the desired product could be obtained.…”
Section: Iron‐catalyzed C−b Bond Formationmentioning
confidence: 99%